Comparative dental anatomy of Bakarwali goat, local sheep of Jammu region and sambar deer - SHALINI, SHALINI; KALITA, A; SARMA, K; ZAMA, M M S (The Indian Journal of Animal Sciences, 2014)
Comparative gross and radiographic anatomical study of dental arches of adult Bakarwali goat, local shecp of Jammu region and sambar deer revealed that incisors were deeply and firmly placed in lower jaw having shovel shaped incisor in goat and sheep, whereas hocky stick like shaped incisors in sambar deer. The length of root was almost twice that of crown of respective incisor. In deer, the root of incisor was curved in central pair and strainght in corner pair, whereas the patternÂ Was reverse in sheep and goat. The 6 cheek teeth on either side of each jaw were placed deep but loose in deer, firmly anchored in sheep. however, in goats they were loosely and shallowly placed. Further the occlusal surface of premolars and molars showed horizontal and vertical lines of dentine in deer which has not been described in any ruminant. Radiographically it was revealed that cheek teeth occupy whole of body of horizontal ramus of mandible. The caudal alveoli for cheek teeth were present even inside the body of vertical ramus of mandible in deer, however, in goat and sheep caudal cheek teeth occupy only anterior 3/4th of body of horizontal ramus of mandible.